Oral keratinocyte stem/progenitor cells: specific markers, molecular signaling pathways and potential uses. (October 2015) - Calenic, Bogdan; Greabu, Maria; Caruntu, Constantin; Tanase, Cristiana; Battino, Maurizio
Abstract: Oral keratinocyte stem cells reside in the basal layers of the oral epithelium, representing a minor population of cells with a great potential to self‐renew and proliferate over the course of their lifetime. As a result of the potential uses of oral keratinocyte stem cells in regenerative medicine and the key roles they play in tissue homeostasis, inflammatory conditions, wound healing and tumor initiation and progression, intense scientific efforts are currently being undertaken to identify, separate and reprogram these cells. Although currently there is no specific marker that can characterize and isolate oral keratinocyte stem cells, several suggestions have been made. Thus, different stem/progenitor‐cell subpopulations have been categorized based on combinations of positive and/or negative membrane‐surface markers, which include integrins, clusters of differentiation and cytokeratins. Important advances have also been made in understanding the molecular pathways that govern processes such as self‐renewal, differentiation, proliferation, wound healing and programmed cell death. A thorough understanding of stem‐cell biology and the molecular players that govern cellular fate is paramount in the quest for using stem‐cell‐derived therapies in the treatment of various oral pathologies. The current review focuses on recent advances in understanding the molecular signaling pathways coordinating the behavior of these cells and in identifying suitable markers used for their isolation and characterization. Special emphasis will also be placed on the roles played by oral keratinocyte stem and progenitor cells in normal and diseased oral tissues and on their potential uses in the fields of general medicine and dentistry.